A Review of the Participation ın the Olympics by Country and the Success ın the Cycling Branch at the Tokyo 2020 Olympic Games - Onur Öztürk, Yusuf Kurt, Mehmet Ilkim, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The popularity of cycling is increasing day by day all over the world. Correspondingly, cycling is involved in more and more branches in the Olympic Games day by day. In addition, it is seen that the number of medals increases depending on the increasing branches. Aim: The research the connection between the success of the countries that won medals in the cycling branch, both and in the general Olympics. In this regard, overall Olympic achievements and achievements in cycling have analyzed in terms of the number of medals won by the countries that won medals in cycling. Methods: The data from the Tokyo 2020 Olympics have been accessed from the official website of the IOC (International Olympic Committee) and the data obtained have been classified in accordance with the purpose. In the statistical analysis, the skewness and kurtosis values of the classified data were analyzed first, and it was determined that the data did not show a normal distribution. In this direction, Spearman correlation analysis was performed in order to determine the connection between the variables. Results: it has been determined that there is a positive and significant connection between the total number of medals won in all branches of the countries that won medals at the Olympics cycling branch and the total number of medals won in the cycling branch. It has also been determined that there is a strong positive connection between the total number of athletes participating at the Olympic cycling branch and the total number of medals won in the countries' cycling branch.